STAGES OF RESISTANCE:POSTCOLONIAL FEMINIST VOICES IN LYNN NOTTAGE’S RUINED (Al-Aasar, 2025)
In this paper, I examine Lynn Nottage’s Ruined (2008) as a modern American drama that engages with the intersections of gender, war, and colonialism in the Democratic Republic of Congo. The play foregrounds strategies of survival and female agency under conditions of sexual violence and systemic oppression, framed through the lens of postcolonial feminism. It further incorporates insights from resistance studies, highlighting how everyday practices such as commerce, song, and storytelling—transform victimhood into resilience on stage. By situating Nottage’s dramaturgy within feminist, postcolonial, and intergenerational debates on gender, trauma, and postcoloniality, the paper argues that Ruined expands the function of theatre, positioning it simultaneously as a witness to violence and as a mode of resistance against endemic oppression.